Working Paper on Population Growth and Natural Resources Pressures in Pursat Catchment - MK16 Project Team (CGIAR Challenge Program on Water and Food, 2013)
This working paper examines population growth in Pursat and its potential impact on food demand and land and water resources in a systematic and integrated manner. The main purpose of the paper is to kick-start a policy debate on population dynamics and food and water security in Pursat. The paper provides background information, observations and empirical analysis of resource demand (real or perceived) associated with population growth and policy decisions related to food and water security.